A Case of Perineurioma Recurring in the Mandible - Kyoko Baba; Yuuta Niimi; Shun Imamura; Ami Kuwabara; Shunichiro Ego; Mitsuru Nemoto; Yasuharu Yamazaki; Akira Takeda (Journal of Plastic and Reconstructive Surgery)
Perineuriomas (PNs) are soft tissue tumors originating from the perineurium. We report the case of a 51-year-old man who presented with a right mandibular mass. Initial examination revealed a palpable, painless, solid mass at the right mandibular angle. Preoperative computed tomography revealed a highly absorbent mass with uneven staining margins in contact with the mandible. Surgery was performed under general anesthesia for diagnosis, and a well-defined solid tumor of 8 cm was excised. Subsequently, immunohistological staining revealed that the tumor was diagnosed with perineuriomas recurrence of mental nerve origin. This is the first report on perineuriomas of mental nerve origin and the third report on recurrent perineuriomas. Our findings highlight the need for immunohistological staining of tumors for perineuriomas diagnosis, and follow-up observation might be recommended given the risk of recurrence.